Outside looking in - Collier, James Lincoln, 1928- (London : Collier Macmillan, 1987)
Ashamed of his parents' way of life traveling around the country peddling honey for medicinal purposes and stealing, Fergy takes his young sister and runs away to find his mother's wealthy parents and a better way to live.
6.6
5-8.